Exploring the experiences and preferences of South Asian patients' of primary care in England since COVID‐19 - Small, Nicola; Masood, Yumna; Stevenson, Fiona; Brown, Benjamin C.; Sanders, Caroline; McMillan, Brian; Atherton, Helen; Mazumdar, Tandrima; Ara, Nigat; Haqqani, Humera; Cheraghi‐Sohi, Sudeh (Health expectations : an international journal of public participation in health care and health policy, 2024)
Introduction Remote (digital and/or telephone) access and consultation models are being driven by national policy with the goal being that the National Health Service operate on a remote‐first (digital‐first) basis by 2029. Previous research has suggested that remote methods of access to care and consulting may act to widen health inequalities for certain patients and/or groups such as those from ethnic minorities. South Asian (SA) patients comprise the largest ethnic minority group in England. Understanding the experiences and needs of this group is critical to ensuring that general practice can deliver equitable, quality health care. Methods Qualitative study. 37 participants (from Indian, Pakistani and/or Bangladeshi background) were recruited to take part in either in‐person preferred language focus groups or remote semistructured interviews in the English language. Thematic analysis was conducted to identify themes in the qualitative data. Findings Three major interlinked themes were identified: (1) reduced access, (2) reduced patient choice and (3) quality and safety concerns. The findings highlight access issues split by (i) general issues with appointment access via any remote means and (ii) specific issues related to language barriers creating additional barriers to access and care. Some patients valued the convenience of remote access but also raised concerns regarding appointment availability and reduced patient choice. Face‐to‐face consultations were preferable but less available. The findings underscore how participants perceived remote care to be of lesser quality and less safe. Concerns were greatest for those with limited English proficiency (LEP), with the removal of non‐verbal aspects of communication and ‘hands‐on’ care leading to perceptions of reduced psycho‐social safety. Conclusion SA patients' experiences of remote‐led primary care access and care delivery were negative with only a minority viewing it positively and for certain limited scenarios. Face‐to‐face models of care remain the preferred mode of consultation, particularly for those with LEP. Hybrid models of access offer patients the greatest choice, and are likely to meet the varying needs of the South‐Asian patient population going forwards. The remote first approach to primary care may be achievable as a service ideal, but its limitations need to be recognised and accounted for to ensure that primary care can be an equitable service, both now and in the future. Public Contribution Members of the public were involved in all phases of research in the study. This included co‐working in partnership throughout the study including, reviewing patient‐facing documents, recruiting participants, data facilitation, translation work, interpretation of the data and co‐authors on this manuscript. The key to the success of our study was collaborative teamwork, which involved experienced members of the public with SA cultural knowledge working together with and integral to the research team for all components.